Haemato-biochemical profiles, body condition and FAMACHA scores at various ages and their interrelations in Surti goats - SORATHIYA, LALITCHANDRA AMNJIBHI; FULSOUNDAR, A.B (Indian Journal of Animal Production and Management, 2017)
The effect of age on haemato-biochemical parameters, BCS and FAMACHA scoring were studied intraditionally reared Surti goats in south Gujarat. Total 240 adult goats, 72 yearlings (1 year to 1st kidding)and 48 kids (Upto 6 month age) were selected for study. All were monitored for FAMACHA and BCSsimultaneously with blood samples collection. The PCV was measured by micro-haematocrit methodand biochemical parameters were measured on biochemical analyzer. BCS and PCV were significantlyhigher in kids and yearlings than adult goats. The younger goats were also having low FAMACHA scoring.Blood glucose, cholesterol, total protein, albumin, A:G ratio, urea, creatinine, calcium, magnesium, ALTand AST did not vary significantly between kids, yearlings or adults Surti goats, whereas, triglycerides andphosphorus were found significantly higher in younger goats and globulin was significantly higher in adultgoats. BCS and PCV have significantly positive whereas FAMACHA has significant negative correlationswith most of blood parameters.